Pelatihan Pembuatan Minuman Probiotik Tepache Siswa MA Muhammadiyah Cambajawaya Kabupaten Gowa - Jumadi, Oslan; Kurnia, Nani; Kusdianawati, Kusdianawati; Azis, Andi Asmawati; Junda, Muhammad (Program Studi Pendidikan IPA Fakultas MIPA Universitas Negeri Makassar, 2025)
A training session on making the probiotic drink tepache was conducted at MA Muhammadiyah Cambajawaya, Gowa Regency, as an educational initiative to promote health and utilize local resources. Tepache is a traditional fermented beverage made from pineapple peel and pulp, rich in probiotics beneficial for digestive health. This activity aimed to enhance students’ understanding of probiotics, train practical skills in producing environmentally friendly fermented drinks, and foster entrepreneurial spirit. The training method included theoretical sessions, live demonstrations, and hands-on practice. Evaluation results showed that the majority of students (87%) expressed interest in making tepache independently and understood its health benefits. The training also introduced the concept of productive use of household organic waste. In conclusion, this activity effectively educated students and opened opportunities for developing local health-based products. Similar training programs are recommended to be expanded with greater institutional and governmental support.